2002
DOI: 10.4049/jimmunol.168.6.2939
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4-MD-2 Complex Mediates the Signal Transduction Induced by Flavolipin, an Amino Acid-Containing Lipid Unique toFlavobacterium meningosepticum

Abstract: Flavolipin, an amino acid-containing lipid isolated from Flavobacterium meningosepticum, induces many immune responses. It has been shown that flavolipin does not induce an immune response of macrophages derived from C3H/HeJ mice, which possess a point mutation in Toll-like receptor 4 (TLR4). To determine whether TLR4 or the molecular complex of TLR4 and TLR4 association molecule MD-2 mediates the flavolipin signal, flavolipin responsiveness was examined by measuring NF-κB activation in Ba/F3 cells and Ba/F3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 37 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…This implies that different anchoring points can lead to dimerization and foresees other possible ways of TLR4 activation that have not been explored until now. It is likely that, in the future, other microbial or endogenous TLR4 stimulators (like amino acid-containing lipid present in many Gram-negative bacteria [ 38 , 39 ], but also gangliosides [ 40 ] or ceramides [ 41 , 42 ], which all share common structural features with diC14-amidine) will be demonstrated to be able to activate TLR4 through interaction with the TLR4 dimerization interface, expanding the possible ligands of TLR4 to non-MD-2-binding lipids. Finally, this new recognition interface might also be involved in the recognition of nanoparticles by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that different anchoring points can lead to dimerization and foresees other possible ways of TLR4 activation that have not been explored until now. It is likely that, in the future, other microbial or endogenous TLR4 stimulators (like amino acid-containing lipid present in many Gram-negative bacteria [ 38 , 39 ], but also gangliosides [ 40 ] or ceramides [ 41 , 42 ], which all share common structural features with diC14-amidine) will be demonstrated to be able to activate TLR4 through interaction with the TLR4 dimerization interface, expanding the possible ligands of TLR4 to non-MD-2-binding lipids. Finally, this new recognition interface might also be involved in the recognition of nanoparticles by the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Gomi et al. showed that the ( R )‐configuration of the lipid moiety in flavolipin is essential for induction of the signals mediated by the TLR4‐MD‐2 complex while the ( S )‐enantiomer did not induce any activation.…”
Section: Fahfas Are Endogenous Lipidsmentioning
confidence: 99%
“…A Ba/F3 cell line introduced with p55Igluc was established previously (26) and was named Ba/luc here. Ba/F3 cell lines were maintained as described previously (25).…”
Section: Methodsmentioning
confidence: 99%